Disruption of a Yeast ADE6 Gene Homolog in Ustilago maydis - M. L. Heidenreich; A. D. Budde; An Zhiqiang; S. A Leong (Fungal Genetics Reports, 2008)
A putative homolog of the Sacharromyces cereviseae ADE6 and Escherichia coli purL genes is identified near a multigenic complex, which contains two genes, sid1 and sid2, involved in a siderophore biosynthetic pathway inUstilago maydis. The putative ADE6 homolog was mutated by targeted gene disruption. The resulting mutant strains demonstrated a requirement for exogenous adenine, indicating that the U. maydis ade6 homolog is required for purine biosynthesis.